Competing landscapes of commerce and tourism: Critical relations and possible strategies in Venice’s historical city - Catalanotti, Cristina (European Spatial Research and Policy, 2023)
This article investigates the relationship between tourism-related economic activities and neighbourhood shops in the historical centre of Venice, in terms of both their spatial distribution and the conflictual uses of the city. In questioning how to inhabit and revitalise the city through commercial activities, the paper wishes to contribute to the discussion proposed in the special number, by presenting a specific yet paradigmatic context and by reflecting on urban regeneration and revitalisation bottom-up practices. The research first unfolds the landscapes of commerce in the city and identifies polarised geographies of tourism-related activities focusing on retail and catering businesses; secondly, it interrogates spatialised strategies that local actors are developing to reflect on their relation with urban planning and policy design processes.